Vertical profiling of Saharan dust with Raman lidars and airborne HSRL in southern Morocco during SAMUM - Tesche, Matthias; Ansmann, Albert; Müller, Detlef; Althausen, Dietrich; Mattis, Ina; Heese, Birgit; Freudenthaler, Volker; Wiegner, Matthias; Esselborn, Michael; Pisani, Gianluca; Knippertz, Peter (Tellus B: Chemical and Physical Meteorology, 2009)
Three groundÃ¢ÂÂbased Raman lidars and an airborne highÃ¢ÂÂspectralÃ¢ÂÂresolution lidar (HSRL) were operated during SAMUM 2006 in southern Morocco to measure height profiles of the volume extinction coefficient, the extinctionÃ¢ÂÂtoÃ¢ÂÂbackscatter ratio, and the depolarization ratio of dust particles in the Saharan dust layer at several wavelengths. Aerosol Robotic Network (AERONET) Sun photometer observations and radiosounding of meteorological parameters complemented the groundÃ¢ÂÂbased activities at the SAMUM station of Ouarzazate. Four case studies are presented. Two case studies deal with the comparison of observations of the three groundÃ¢ÂÂbased lidars during a heavy dust outbreak and of the ground lidars with the airborne lidar. Two further cases show profile observations during satellite overpasses on May 19 and June 4, 2006. The height resolved statistical analysis reveals that the dust layer depth typically reaches 4Ã¢ÂÂ6 km height above sea level (asl), sometimes even 7 km. A vertically inhomogeneous dust plume with internal dust layers was usually observed in the morning before the evolution of the boundary layer starts. The Saharan dust layer was wellÃ¢ÂÂmixed in the early evening. The 500 nm dust optical depth ranged from 0.2Ã¢ÂÂ0.8 at the field site to the south of the High Atlas mountains, Angstrom exponents derived from photometer and lidar data were between 0Ã¢ÂÂ0.4. The volume extinction coefficients (355, 532 nm) varied from 30Ã¢ÂÂ300 Mm -1 with a mean value of 100 Mm -1 in the lowest 4 km a.s.l. On average, extinctionÃ¢ÂÂtoÃ¢ÂÂbackscatter ratios of 53Ã¢ÂÂ55 sr (ÃÂ±7Ã¢ÂÂ13 sr) were obtained at 355, 532, and 1064 nm.